De novo 12q22.q23.3 duplication associated with temporal lobe epilepsy. (August 2017) - Vari, Maria Stella; Traverso, Monica; Bellini, Tommaso; Madia, Francesca; Pinto, Francesca; Minetti, Carlo; Striano, Pasquale; Zara, Federico
Abstract: Purpose: Temporal lobe epilepsy (TLE) is the most common form of focal epilepsy and may be associated with acquired central nervous system lesions or could be genetic. Various susceptibility genes and environmental factors are believed to be involved in the aetiology of TLE, which is considered to be a heterogeneous, polygenic, and complex disorder. Rare point mutations in LGI1, DEPDC5, and RELN as well as some copy number variations (CNVs) have been reported in families with TLE patients. Methods: We perform a genetic analysis by Array-CGH in a patient with dysmorphic features and temporal lobe epilepsy. Results: We report a de novo duplication of the long arm of chromosome 12. Conclusion: We confirm that 12q22-q23.3 is a candidate locus for familial temporal lobe epilepsy with febrile seizures and highlight the role of chromosomal rearrangements in patients with epilepsy and intellectual disability.